Tinjauan terhadap Kualitas Kerja Karyawan Berdasarkan Pengalaman Kerja dan Motivasi pada PT. Latexindo Toba Perkasa Kabupaten Deli Serdang - Utama, Amrin Mulia (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to find out) The effect of work experience and motivation variables on employee performance of PT. Latexindo Toba Perkasa Deli Serdang District This research is categorized as associative research. Samples taken were 55 employees of PT. Latexindo Toba Perkasa Deli Serdang District. Data analysis techniques in this study are multiple linear regression analysis techniques. The research data comes from primary data and the process of collecting data using interviews and questionnaires. From the results of the study obtained Work experience has a significant positive effect on employee performance, where t is equal to 3,714 > t table 1.67469 with a significance of 0.000 <0.005. Motivation has a significant positive effect on employee performance where t count is 3,511 > t table 1.67469 with significance 0.001 <0.005. Work experience and motivation influence simultaneously on employee performance where F count is 38,575 with a significance level of 0,000 < 0.005. The calculated F value is 38.575 and F table 3.18. Significance value 0.001 < 0.005.